Post-patterning of an electronic homojunction in atomically thin monoclinic MoTe2. (8th February 2017) - Kim, Sera; Kim, Jung Ho; Kim, Dohyun; Hwang, Geunwoo; Baik, Jaeyoon; Yang, Heejun; Cho, Suyeon
Abstract: Monoclinic group 6 transition metal dichalcogenides (TMDs) have been extensively studied for their intriguing 2D physics (e.g. spin Hall insulator) as well as for ohmic homojunction contacts in 2D device applications. A critical prerequisite for those applications is thickness control of the monoclinic 2D materials, which allows subtle engineering of the topological states or electronic bandgaps. Local thickness control enables the realization of clean homojunctions between different electronic states, and novel device operation in a single material. However, conventional fabrication processes, including chemical methods, typically produce non-homogeneous and relatively thick monoclinic TMDs, due to their distorted octahedral structures. Here, we report on a post-patterning technique using laser-irradiation to fabricate homojunctions between two different thickness areas in monoclinic MoTe2 . A thickness-dependent electronic change from a metallic to semiconducting state, resulting in an electronic homojunction, was realized by the optical patterning of pristine MoTe2 flakes, and a pre-patterned device channel of monoclinic MoTe2 with a thickness-resolution of 5 nm. Our work provides insight on an optical post-process method for controlling thickness, as a promising approach for fabricating impurity-free 2D TMDs homojunction devices.